HUBUNGAN STATUS GIZI DAN AKTIVITAS OLAHRAGA DENGAN TINGKAT KEBUGARAN JASMANI ( STUDI PADA SISWA KELAS VIII SMP NEGERI 1 KEDIRI ) - YUDI IRIANTO, FEBRI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Nutrient status is a body condition as a consequences of food intake and nutrient substances on certain variable form that can be measured with certain methods. Low or abnormal   nutrient status will affect to physical fitness. Since nutrient status is one of factors that affect physical fitness level. Regular and not overdoing sport activity will cause fitness above average and by performing sport activity exercise will cause higher physical fitness level. So that the effect to physical fitness have bigger percentage. The aim of this research is to know correlations of nutrient status and sport activity with physical fitness level of eight grade student of SMP Negeri 1 Kediri. This is a non-experiment research with quantitative approach and correlational design. Population in this research is all eight grade student of SMP Negeri 1 Kediri that amounted of 270 students. While sample collection technique that applied is cluster sampling with sample amount as big as 47 students. Instrument in this research is IMT/U for nutrient status, sport activity questioner, TKJI test to measure physical fitness level. Data analysis that applied is logistic regression. Based on data analysis result it can be unknown that nutrient status have significant score 0,024 <ρvalue (sig) 0,05, with determination coefficient as big as 42,5%, so Ho1 is rejected and Ha1 is accepted. Thus, there is correlations between nutrient status with physical fitness as big as 42,5%. While sport activity have signification score 0,817 >ρvalue (sig) 0,05 so Ho2 is accepted and Ha2 rejected. Thus, there is not correlation between nutrient status and sport activities with physical fitness level.   Thus, it can be conclude that there is not significant correlation between nutrient status dan sport activity with physical fitness level on eight grade student of SMP Negeri 1 Kediri. Keywords: nutrient status, sport activity, physical fitness